Early age behaviour of recycled concrete aggregates under normal and severe drying conditions. (September 2017) - Souche, Jean-Claude; Bendimerad, Ahmed Z.; Roziere, Emmanuel; Salgues, Marie; Devillers, Philippe; Garcia-Diaz, Eric; Loukili, Ahmed
Abstract: The use of recycled aggregates in concrete mixtures is a part of waste recovery strategy. The French national project RECYBETON aims at developing scientific knowledge to facilitate the use of recycled aggregates into concrete. In this experimental study, two exposure conditions were combined to analyse the behaviour of fresh and hardening concrete in standard and severe drying conditions (8 m s −1 wind speed). High evaporation rate promotes the development of plastic shrinkage and cracking of fresh concrete. The influence of recycled concrete aggregates proportion and initial water saturation rate were investigated. Two series of concrete mixtures were designed to reach two strength classes. The strains and weight loss of concrete samples were monitored until the stabilization of plastic shrinkage. The increase in evaporation rate accelerated the development and increased the maximum value of plastic shrinkage but did not significantly influence the shrinkage-to-weight loss ratios. In severe conditions plastic shrinkage developed before initial setting thus reached higher magnitudes. The main mix-design parameter affecting the shrinkage-to-weight loss ratio and cracking was the total water-to-binder ratio. The total water content includes the water added and the water used to pre-saturate the aggregates. High evaporation rate triggered the release of water initially absorbed by recycled concrete aggregates. Highlights: The effect of two drying conditions on plastic shrinkage of recycled concrete was investigated. The plastic shrinkage vs. weight loss curves were characterized by three stages. The initial water saturation significantly affected the plastic shrinkage and cracking sensitivity of fresh concrete. It is necessary to adapt the curing methods under severe drying conditions.